2015
DOI: 10.5137/1019-5149.jtn.15330-15.0
|View full text |Cite
|
Sign up to set email alerts
|

Gamma knife radiosurgery for arteriovenous malformations: clinical series of 199 patients

Abstract: ABSTRACTconsiderable effects on the patient's work activity and quality of life (8,17,22,30).AVMs can be treated with microsurgery, stereotactic radiosurgery (RS) and endovascular embolization (8). Surgical removal is the initial treatment of choice in appropriate patients as it removes immediate relief from hematoma in ruptured AVMs and decreases the bleeding risk (3,8,38). However, rates of permanent morbidity and mortality related to microsurgery range between 3.9-25% and 0.7-4.2%, respectively (3,4,8,12,15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…54 These findings suggest that the pathophysiology of delayed cyst formation is distinct from that of post-SRS hemorrhage. 2,15,34,65,66 Indeed, histopathological examination of resected cysts suggests that cyst formation occurs secondary to a chronic, organized response to radiation-induced vascular telangiectasia and wall damage, which promotes microhemorrhage and protein exudation. 59 It is possible that prior AVM hemorrhage and embolization increase tissue susceptibility to damage, thereby increasing the risk of cyst formation.…”
Section: Factors Associated With Post-srs Cyst Formationmentioning
confidence: 99%
“…54 These findings suggest that the pathophysiology of delayed cyst formation is distinct from that of post-SRS hemorrhage. 2,15,34,65,66 Indeed, histopathological examination of resected cysts suggests that cyst formation occurs secondary to a chronic, organized response to radiation-induced vascular telangiectasia and wall damage, which promotes microhemorrhage and protein exudation. 59 It is possible that prior AVM hemorrhage and embolization increase tissue susceptibility to damage, thereby increasing the risk of cyst formation.…”
Section: Factors Associated With Post-srs Cyst Formationmentioning
confidence: 99%
“…Thirty-three (97%) studies were from single centres and one (3%) was multi-centre (Appendix 7 ). Thirteen (39%) studies were from North America [ 4 , 14 16 , 18 , 41 , 43 45 , 52 , 56 , 66 , 74 ], 12 (36%) from Asia [ 5 , 6 , 8 , 31 , 32 , 36 , 39 , 46 , 47 , 51 , 57 , 75 ] and 8 (24%) from Europe [ 2 , 24 , 35 , 49 , 54 , 58 , 65 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Complete nidus obliteration, confirmed on angiography imaging, was achieved in 56.7% (3092/5450) of patients in 21 cohorts, at the end of follow-up after single-stage Gamma knife treatment [ 5 8 , 14 16 , 24 , 31 , 32 , 36 , 39 , 46 , 47 , 49 , 51 , 52 , 54 , 57 , 58 , 65 ]. Overall nidus obliteration, confirmed with either angiography or MRI imaging, was achieved in 67.8% (4605/6792) of patients in 29 cohorts, at the end of follow-up after single-stage Gamma knife treatment [ 2 , 4 8 , 14 16 , 18 , 24 , 31 , 32 , 36 , 39 , 46 , 47 , 51 , 52 , 54 , 56 58 , 64 , 65 , 71 , 74 , 75 ]. Table 3 outlines AVM GKRS obliteration outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pan et al suggested that delayed cyst formation follows a disparate pathophysiological course compared with that of post-SRS hemorrhage. 4,12,34,45,57,58 Delayed radiation effects were observed with both chronic encapsulated expanding hematoma and nodular lesion. 50 Microscopically, these lesions revealed damage to dilated capillary walls with protein exudate, hyalinization and fibrinoid necrosis, and microhemorrhage.…”
Section: Proposed Mechanisms Of Post-srs Cyst Formationmentioning
confidence: 99%